What Do We Know About Gangs and Gang Members and Where Do We Go From Here? - Decker, Scott H.; Melde, Chris; Pyrooz, David C. (Justice quarterly, 2013)
This review provides an opportunity to assess the current state of gang research and suggest directions for its future. There has been a dramatic increase in research on gangs, gang members, and gang behavior since the early 1990s, making this review especially timely. We use Short's three-level framework of explanation to organize the findings of prior research, focusing on individual-, micro-, and macro-level research. Attention is focused on the findings of such research, but we also examine theoretical and methodological developments as well. Drawing from Short and life-course research, we introduce a cross-level temporal framework to guide future directions in gang research.